2022
DOI: 10.1177/21676968221121165
|View full text |Cite
|
Sign up to set email alerts
|

Does the Gender of Your Friends Matter for Sexist Attitudes About Women?

Abstract: Building upon two complimentary theoretical frameworks related to group relations (i.e., Intergroup Contact Theory and Peer Exposure), we examined how emerging adults’ friendships with men and women were related to their hostile sexism, benevolent sexism, and sexual objectification attitudes. Participants were 212 college students ( M age = 20.20 years, SD = 2.08; 62% female; 58% White) from a large southwestern university. Results provided support for Intergroup Contact Theory and for a Peer Exposure effect, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 84 publications
2
7
0
Order By: Relevance
“…Contact with same-gender friends was also associated with gender prejudice, specifically with more benevolent sexism, more gender-inequality beliefs, and, only for men, with more hostile sexism. These findings could be explained in light of the hydraulic effects also found in previous research on intergroup contact showing that when outgroup contact increases, ingroup contact decreases, and that having more outgroup contact decreased prejudice, whereas having more ingroup contact increased prejudice ( Jenkins et al, 2022;Levin et al, 2003). The current study indeed found a negative association between the amount of contact with same-gender and other-gender friends, and having more outgroup friends decreased (some) gender-prejudice beliefs, whereas having more ingroup friends increased gender-prejudice beliefs.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…Contact with same-gender friends was also associated with gender prejudice, specifically with more benevolent sexism, more gender-inequality beliefs, and, only for men, with more hostile sexism. These findings could be explained in light of the hydraulic effects also found in previous research on intergroup contact showing that when outgroup contact increases, ingroup contact decreases, and that having more outgroup contact decreased prejudice, whereas having more ingroup contact increased prejudice ( Jenkins et al, 2022;Levin et al, 2003). The current study indeed found a negative association between the amount of contact with same-gender and other-gender friends, and having more outgroup friends decreased (some) gender-prejudice beliefs, whereas having more ingroup friends increased gender-prejudice beliefs.…”
Section: Discussionsupporting
confidence: 66%
“…Friendships also provide an interesting context to examine effects of both outgroup and ingroup contact. Previous research demonstrated so-called 'hydraulic effects' evident in a negative association between the numbers of ingroup and outgroup friends, and more outgroup friends, but less ingroup friends, being associated with less prejudiced beliefs ( Jenkins et al, 2022;Levin et al, 2003).…”
Section: Friendship As An Important Type Of Intergroup Contactmentioning
confidence: 99%
See 3 more Smart Citations